Physical exercises and massage influence on the organism of school age children with violations of carriage in a frontal plane. - Kruzhylo Galina Grigor'evna; Zimenko Elena Vladimirovna (Kharkov National Pedagogical University, 2011)
Scientific researches results on the subject of efficiency evaluation of the physical exercises and massage influence on the carriage of school age (7 - 14years) children are adduced. School age children total number of 20 (10 girls and 10 boys) with backbone scoliotic curvatures of I - II degree took part in the experiment. There were applied: physical exercises (forming of carriage, unloading of spine, trunk muscles endurance development, exercises in an equilibrium), classic and segmentary massage. It is well-proven that a neat rehabilitation complex rendered effective influence on a carriage probed experimental group by comparison to the children of control group.